A comprehensive numerical approach for modelling blind-bolted CFST connections. (October 2021) - Debnath, Partha Pratim; Chan, Tak-Ming
Abstract: Conducting numerical investigation for the behaviour of a blind-bolted connection with concrete-filled steel tube (CFST) and an open steel section could emerge with several convergence issues due to its complex mechanism and interactions between the connection components. This paper attempts to identify and address these issues and provide reliable solution techniques that can be adopted to achieve convergence and accurately predict the behaviour of blind-bolted CFST connections. Three different types of blind-bolts, which are currently used in experimental research, have been considered in this study. Primarily, the paper addresses the blind-bolt modelling aspects, application of bolt preload, identification of interaction surfaces, use of mass-scaling option, system energy issues and non-linear material modelling. For accurate representation of concrete compressive crushing and tensile cracking, the existing available material models with damage criteria have also been discussed. Sensitivity analyses have also been conducted for such connections which will complement the reliability of the numerical models. The generated numerical models are in good agreement with existing experimental counterparts. Thus, the techniques discussed can be adopted for a comprehensive modelling and understanding of blind-bolted CFST connections with reduced computational cost, and help making rational design for future experimental tests.